Low Relative Handgrip Strength Is Associated with a High Risk of Non-Alcoholic Fatty Liver Disease in Italian Adults: A Retrospective Cohort Study - Samantha Maurotti; Roberta Pujia; Elisa Mazza; Maria Francesca Pileggi; Franco Arturi; Maria Grazia Tarsitano; Tiziana Montalcini; Arturo Pujia; Yvelise Ferro (Applied Sciences, 2023)
Background: Non-alcoholic fatty liver disease (NAFLD) and the presence of low muscle mass (sarcopenia) represent noteworthy health issues. Handgrip strength, a muscle function indicator, is vital for sarcopenia diagnosis. We investigated the link between handgrip strength and hepatic steatosis in Italian adults. Methods: We retrospectively assessed 388 adults (≥50 years), measuring muscle function and hepatic steatosis using a dynamometer and transient elastography. We divided participants into handgrip strength tertiles. Results: 207 had NAFLD. The lowest handgrip strength tertile had a higher NAFLD prevalence (64% vs. 46%, p = 0.02). Tertiles I and II exhibited increased odds of NAFLD in comparison to tertile III, with an odds ratio of 5.30 (95% confidence interval: 2.24–12.57, p < 0.001) and 2.56 (95% confidence interval: 1.17–5.59, p = 0.01), respectively. rHGS predicted NAFLD with an AUC of 0.41 (SE = 0.029, p = 0.003). An rHGS of 1.22 achieved 18% sensitivity and 80% specificity for hepatic steatosis prediction. Conclusion: Low handgrip strength is linked to an increased susceptibility to NAFLD among the Italian population, implying its potential utility in the identification of risk for hepatic steatosis.